Urban Transport Development A Complex Issue - Jönson, Gunella; Tengström, Emin (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Urban Transport Development is a contribution to the ongoing global discussion on the future of urban transport. The main themes are how to cope with the complexity of urban transport development and the process of change including its determining factors. The role of leadership in the development process is the key issue. Main areas of discussion are the historical background, the diversity and complexity of present problems, and the outcome of attempts to promote positive future development in urban environments around the world.